1993
DOI: 10.1111/j.1440-169x.1993.00395.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Sensitivity of a Hybrid between Two Species of Sea Urchin Differing in Thermotolerance

Abstract: Eggs of Dendraster excentricus can be fertilized with sperm of Strongylocentrotus purpuratus at a high success rate according to Whiteley and Baltzer's method. The resulting hybrids are well suited for investigations of the factors determining embryonic thermosensitivity, because the embryos of both the above species differ significantly with regard to egg size, blastula shape, and particularly thermotolerance and the temperature dependence of their developmental rate. Morphologically, the hybrids show some pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…• C) underwent normal development, although the development time varied at different temperatures, which is in line with the findings of others (Matsumoto et al 1988;Fujisawa 1993). The synchronized or asynchronized development of larvae is another point to be considered in order to understand the mode of development (Rahman et al 2007).…”
Section: Discussionsupporting
confidence: 86%
“…• C) underwent normal development, although the development time varied at different temperatures, which is in line with the findings of others (Matsumoto et al 1988;Fujisawa 1993). The synchronized or asynchronized development of larvae is another point to be considered in order to understand the mode of development (Rahman et al 2007).…”
Section: Discussionsupporting
confidence: 86%
“…The findings of our study were also the same as Rahman et al (2007), who found abnormality in the early development and larval growth of sea urchin (Echinometra mathaei) beyond the low (16 o C) and high temperature (34 o C) levels. Similar results were also observed in other temperate and tropical species of Indo-Pacific sea urchins (Matsumoto et al, 1988;Fujisawa, 1993;Sarifudin et al, 2016).…”
Section: Discussionsupporting
confidence: 83%
“…Observations were also made at every 30 min interval. The time taken for 50% of the embryo and larva to reach each progressive stage was recorded (Fujisawa, 1993;Rahman et al, 2002). Development stage(s) were assessed for the first 50 embryos observed under a compound light microscope at 10x magnification.…”
Section: Early Developmentmentioning
confidence: 99%
“…Some reports indicated that sympatric echinoid species are isolated by prezygotic isolating barriers including differences in microhabitats, breeding seasons (Lessios 2007), environmental conditions like temperature (Fujisawa 1993) and alkalinity (Tennent 1910). On the coasts of Yamaguchi area, we can find the adults of the temnopleurids, and we made field survey over 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…In other hand, Onoda (1938) formed hybrids between 10 different species representing 2 orders, 6 families and 10 genera and indicated that in hybrid skeletogenesis the maternal influence is generally stronger than the paternal one. It was also reported that the thermotolerance depends on the egg cytoplasm in hybrids of a dendrasterid Dendraster excentricus (Eschscholtz, 1831) and S. purpuratus (Fujisawa 1993). Additionally, tropical echinometrids, Echinometra mathaei (Blainville, 1825) and E. oblonga (Blainville, 1825) or E. sp.…”
Section: Introductionmentioning
confidence: 97%